A MICROPROPAGATION AND ACCLIMATIZATION OF LYCIUM BARBARUM L. MICROPLANTS TO EX VITRO CONDITIONS - Mihaela Cioloca; Andreea Tican; Monica Popa; Adrian Nicolae (Agricultura)
With a high content of antioxidants, vitamins, amino acids, essential minerals and essential fatty acids, goji (Lycium barbarum L.) contributes to general well-being, supports the immune system, being considered a superfood. Goji berries have a long history of medicinal use, they are considered to have an important antidiabetic, anti-aging and anticancer effect, repair epidermal lesions, provide benefits to the cardiovascular system and contribute to effective cholesterol control. Micropropagation techniques are used as biotechnological tools that allow the production of a large number of plants from small fragments taken from a mother plant in a relatively short period of time. An applicable and efficient protocol for sterilization, initiation, multiplication, rooting and acclimatization in goji was developed. The results obtained in this study highlight the usefulness of tissue cultures in obtaining a high-quality planting material and the use of healthy biological material produced in vitro for large-scale propagation in ex vitro conditions.